Divergenz in europäischen Grenzregionen und die moralische Legitimität der Wohnmigration - Boesen, Elisabeth (Borders in Perspective UniGR-CBS Thematic Issue. Grenzüberschreitende Ungleichheiten in der Großregion | Inégalités transfrontalières dans la Grande Région, 2025)
Abstract: „Der Beitrag befasst sich mit luxemburgischen Bewohnern deutscher Grenzdörfer, d. h. mit einer Gruppe von Migranten, bei der das bei Migrationsvorgängen gemeinhin anzutreffende Ungleichheitsverhältnis nicht vorherrscht, ja teilweise ins Gegenteil verkehrt ist: Die Migranten sind hier nicht arm und benachteiligt, sondern sozio-ökonomisch häufig überlegen und in bestimmten Bereichen, etwa dem des Arbeitsmarktes, privilegiert. Die Analyse der Umzugsgeschichten zeigt jedoch, dass die Migranten mit Problemen konfrontiert sind, die aus der Divergenz der Entwicklungen diesseits und jenseits der Grenze herrühren. Die Beschäftigung mit diesen ‚privilegierten Migranten‘ ist nicht nur im Zusammenhang mit Mobilitätsphänomenen und Ungleichheitsverhältnissen in (west)europäischen Grenzräumen von Belang, sondern auch aufschlussreich im Hinblick auf das generelle Problem der moralischen Legitimität der Migration, das sich in ihrem Fall besonders deutlich stellt: Was rechtfertigt das Verlassen des Herkunftslandes, und womit kann der Anspruch auf das Leben am neuen Ort begründet werden?“
Keywords: Arbeitsmarkt; Grenzarbeitnehmer; Sozialraum; Wohnen; Wohnungsmarkt

Border-Crossing and “Temporal Otherness” in the Greater Region SaarLorLux. Residential Migrants’ Experiences of Divergence - Boesen, Elisabeth (Borders in Globalization Review, 2024)
Abstract: „This article deals with border-crossing and the experiences of “temporal otherness” of residential migrants who move their home from Luxembourg to the German side of the River Moselle. Research on temporal borders is highly influenced by a particular spatio-political relation: the West creating its underdeveloped other and coping with this other by controlling border-crossing, which in turn results in maintaining the idea of the other’s temporal remoteness. The Luxembourgish–German border region offers a complement to this perspective; here, one encounters migrants who move in the opposite temporal direction and appreciate certain forms of “being behind” in their new place of residence. These migrants must cope with divergences, i.e., with the fact that economic and socio-cultural conditions within their new socio-spatial universe, the cross-border region, have evolved differently. This article argues that the analysis of migrants’ memories is illuminating with respect to the question of the moral legitimacy of moving, and thus regarding the conception and everyday construction of cross-border communities. It sheds light on the fact that borderland research—by focusing on national differences and related conceptions of cross-border mobility and exchange—tends to ignore borderlanders’ notions of (regional) unity and related claims for convergence.“
Keywords: Fremdheit; Grenzarbeitnehmer; Mobilität; Sozialraum

Borderland Child Heterotopias. A Case Study on the Belgian-German Borderlands - Venken, Machteld (Journal of Borderlands Studies, 2021)
Abstract: „This article investigates the capacities of children to participate actively in their lives in the Belgian-German borderlands in the time period between World War I and World War II. The article interprets a body of historical sources that has hitherto been left unexplored – namely, borderland child ego documents – with the help of insights from child studies and border studies. These ego documents unfold as borderland child heterotopias. Borderland child heterotopias include material places and creative linguistic loci established by or for those considered in crisis in relation to the rest of society based on their age within or outside child spaces of modernity. The borderland child heterotopias offer a unique gateway to borderland children’s past imaginations for a better world.“
Keywords: Grenzgebiet; Kind; Sozialraum

Dwelling in (Un)Familiarity. Examples from the Luxembourg-German Borderland - Boesen, Elisabeth; Schnuer, Gregor (European Borderlands. Living with Barriers and Bridges, 2017)
Keywords: Grenzarbeitnehmer; Sozialraum

Cross-border residential mobility of people working in Luxembourg. Developments and impacts - Nienaber, Birte; Pigeron-Piroth, Isabelle (European Borderlands. Living with Barriers and Bridges, 2017)
Keywords: Grenzarbeitnehmer; Sozialraum

Socio-cultural proximity, daily life and shopping tourism in the Dutch–German border region - Szytniewski, Bianca; Spierings, Bas; Velde, Martin van der (Tourism Geographies, 2016)
Abstract: „This paper analyses feelings of socio-cultural proximity and distance with a specific focus on the tourist experience in cross-border shopping and everyday life practices in border regions. We examined shopping practices of Dutch border crossers who visit the German town Kleve in the Dutch–German border region. This particular border context has allowed us not only to reflect on a multidimensional approach towards socio-cultural proximity and distance, but also to examine how these different dimensions express themselves in the tourist experience when it comes to people and places that are geographically ‘close’ but assumingly socially and culturally ‘distant’ from home. Although some differences prompted feelings of discomfort, in particular, differences in social engagement, feelings of comfort stand out in our analysis of cross-border shopping tourism. Furthermore, our study shows that shopping tourism and exoticism, on the one hand, and everyday routines and the mundane, on the other hand, are closely intertwined in the lives of people living in a border region, resulting in a fluid interpretation of the exotic and the mundane in the cross-border context.“
Keywords: Einkaufen; Grenzgebiet; Kleve (Kreis Kleve); Mobilität; Sozialraum; Tourismus; Verbrauch

Impacts de la mobilité résidentielle transfrontalière sur les espaces de la vie quotidienne des actifs du Luxembourg - Gerber, Philippe; Carpentier-Postel, Samuel (Economie et Statistique, 2012)
Abstract: „À partir d'une enquête effectuée par le CEPS/INSTEAD et la fondation Forum Europa, cet article analyse le phénomène de mobilité résidentielle transfrontalière et son impact sur les déplacements quotidiens. Réalisée au printemps 2008, cette enquête porte sur les actifs occupés résidant initialement au Luxembourg qui se sont installés dans un pays frontalier entre 2001 et 2007, tout en conservant leur emploi au Grand-Duché. Pour un grand nombre d'entre eux, le déménagement transfrontalier a permis d'accéder à un logement plus grand, voire d'en devenir propriétaire. Néanmoins, l'analyse des déplacements quotidiens montre que la grande majorité de ces personnes a dû consentir à de nombreuses concessions en termes de mobilité pour accéder au logement souhaité. Cela se ressent particulièrement pour le trajet domicile/travail dont la distance moyenne a doublé, ce qui a renforcé la dépendance des personnes concernées vis-à-vis de l'automobile. En dehors même du travail, la localisation des autres activités quotidiennes se trouve modifiée à la suite du déménagement. Des indicateurs synthétiques issus de la géostatistique permettent d'analyser la reconfiguration des lieux de ces activités. Malgré la relocalisation de beaucoup d'entre elles autour du nouveau lieu de résidence, une certaine inertie des comportements se traduit par le maintien de près d'une activité sur trois au Luxembourg. Dès lors, la dispersion des espaces d'activités augmente pour certains enquêtés. Cette dispersion, liée à la part des activités transférées vers le pays de résidence, varie fortement selon la nationalité; elle est plus forte pour les Luxembourgeois et pour les Portugais. Les personnes originaires des régions frontalières, qui retournent dans leur pays d'origine, gardent également près d'un quart de leurs activités au Grand-Duché: cela témoigne à la fois de l'importance du lieu de travail dans la structuration des espaces de vie quotidienne et d'un capital spatial déjà mis en évidence dans le cas d'actifs résidant au Luxembourg.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

Zum Modell des transnationalen sozialen Raums im Kontext von Grenzregionen. Theoretisch-konzeptionelle Überlegungen am Beispiel des Grenzgängerwesens - Wille, Christian (Europa Regional, 2009)
Abstract: „Angesichts fortschreitender Globalisierung gewinnen übernationale Sozialbeziehungen zunehmend an Bedeutung. Sie rücken als Forschungsgegenstände immer stärker in die Human- und Sozialwissenschaften ein und stellen die teilweise noch an ‚verankerten’ Lebensbedingungen orientierten analytischen Konzepte in Frage. So ist teilweise ein Wandel weg von statischen, homogenisierenden und abgeschlossenen Modellen von Gesellschaft, Kultur und Raum hin zu entsprechend offenen und dynamischen Konzepten auszumachen. Diese können wichtige Impulse geben für Fragestellungen und ihre theoretischen Annäherungen auf der kleinräumigen Ebene von benachbarten Grenzregionen. Im vorliegenden Beitrag soll hierfür das Modell des transnationalen sozialen Raums aufgegriffen und im Hinblick auf grenzüberschreitende Sozialverflechtungen zwischen europäischen Grenzregionen theoretisch-konzeptionell diskutiert werden. Dafür werden zunächst die Mobilitätstypen des Transmigranten und des Grenzgängers erläutert und auf empirischer Ebene beispielhaft Bezüge zu einer bei Grenzgängern in der „Großregion SaarLorLux“ durchgeführten Studie hergestellt. Das im Umfeld der Migrationsforschung entwickelte und vorzustellende Modell fokussiert auf dauerhafte Sozialzusammenhänge, die über Nationalstaaten hinausreichen und neue Vergesellschaftungszusammenhänge konstituieren, gleichwohl bleibt es in seiner Konzeption und Analytik weitgehend einem statischen und nationalstaatlichen Denken verhaftet. Vor diesem Hintergrund wird versucht, die zentralen Desiderata und mögliche Entwicklungsperspektiven für die Erforschung transnationaler Sozialzusammenhänge in Grenzregionen herauszuarbeiten. Given the continuing processes of globalisation, social networks that can be categorised as being above the national level are coming to the fore. They are also making constant headway as research topics in the human and social sciences by calling analytical concepts into question that are still geared towards “rooted” life conditions. For instance, there is a move away from statistical, homogenising and closed models of society, culture and space to more open and dynamic concepts that can provide important motivation for questions and their way they theoretically approach these issues on the small-space level of neighbouring border regions. This article will address the model of a transnational social space and discuss it in the framework of cross-border social interconnections between European border regions. It will start off by explaining the types of mobility that transmigrants and cross-border commuters have and then empirically and exemplarily linking this to a study made on cross-border commuters in the large-scale SaarLorLux region. The model to be presented here has been developed in the context of migration research and it focuses on permanent social connections that go beyond national states and constitute new connections of socialisation, even though its conception and analytical methods mostly remain dedicated to static thinking and to the national state. Given these facts, this article attempts to outline the central desiderata and potential development vistas for the research on transnational social relationships in border regions.“
Keywords: Arbeitnehmer; Arbeitsmigration; Grenzarbeitnehmer; Mobilität; Pendler; Sozialraum; Transnationalisierung

Elastic Migration. The Case of Dutch Short-Distance Transmigrants in Belgian and German Borderlands - Houtum, Henk van; Gielis, Ruben (Tijdschrift voor Economische en Sociale Geografie, 2006)
Abstract: „Along the Dutch-Belgian and Dutch-German border a new and interesting kind of transmigration is developing, that is migration over only a few kilometres across the border. The main characteristic of these Dutch short-distance transmigrants is that they have their houses in Belgium/Germany, but their social and working life still takes place in the Netherlands. Their transmigration is hence very elastic. This elasticity invokes the interesting question: what kind of (trans)national identity these Dutch are displaying and to what extent the Dutch desire to be and/or are socially provoked to be integrated in the neighbouring Belgian/German society. These cross-border spaces in which the short-distance migrants have their residences could very well be interesting micro-scale laboratories of the future of the nation-state in the European Union.“
Keywords: Grenzarbeitnehmer; Mobilität; Sozialraum; Wohnungsmarkt

Spheres of Transnationalism within the European Union. On Open Doors, Thresholds and Drawbridges along the Dutch–German Border - Strüver, Anke (Journal of Ethnic and Migration Studies, 2005)
Abstract: „This article addresses the European Union's claim to establish transnational spaces through co-operation across its internal borders. Focusing on the Dutch–German borderland as an example, people's practices towards this border and their perceptions of it are introduced. It is underscored that these practices are influenced by popular representations, which (re)produce bounded spaces and the barrier effect of the border, thus making it difficult to imagine a transnational space. This observation is complemented by the phenomenon that—due to a housing shortage in the Netherlands—Dutch people have recently begun to move to German places directly on the border, although they maintain their jobs in the Netherlands. Concentrating specifically on one of these German villages, Kranenburg, the emergence of a community of transmigrants is highlighted in order to reflect upon the question of whether this form of frequent short-distance border crossing fosters a European transnational sphere.“
Keywords: Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Kranenburg (Kleve); Sozialraum; Transnationalisierung